2020
DOI: 10.3390/molecules25092087
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Understanding of Peptide Analogues, DALDA, [Dmt1]DALDA, and KGOP01, Binding to the Mu Opioid Receptor

Abstract: The mu opioid receptor (MOR) is the primary target for analgesia of endogenous opioid peptides, alkaloids, synthetic small molecules with diverse scaffolds, and peptidomimetics. Peptide-based opioids are viewed as potential analgesics with reduced side effects and have received constant scientific interest over the years. This study focuses on three potent peptide and peptidomimetic MOR agonists, DALDA, [Dmt1]DALDA, and KGOP01, and the prototypical peptide MOR agonist DAMGO. We present the first molecular mode… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 55 publications
(111 reference statements)
1
19
0
Order By: Relevance
“…It is commonly recognized that hits identified in a virtual screening campaign often display weaker activity than the compounds the models were based on 26 , 53 . Our docking study to the MOR revealed that both compounds share several essential receptor-ligand interactions, including the salt bridge with Asp147 and hydrogen bond formation with Tyr148 (water-mediated in the case of corydaline ( 2 ), analogous to BU72), as two residues recognized as key interaction sites for ligand (small molecules and peptides) binding to the MOR 24 34 , 54 . However, there are also receptor-ligand interaction pattern dissimilarities.…”
Section: Discussionmentioning
confidence: 94%
“…It is commonly recognized that hits identified in a virtual screening campaign often display weaker activity than the compounds the models were based on 26 , 53 . Our docking study to the MOR revealed that both compounds share several essential receptor-ligand interactions, including the salt bridge with Asp147 and hydrogen bond formation with Tyr148 (water-mediated in the case of corydaline ( 2 ), analogous to BU72), as two residues recognized as key interaction sites for ligand (small molecules and peptides) binding to the MOR 24 34 , 54 . However, there are also receptor-ligand interaction pattern dissimilarities.…”
Section: Discussionmentioning
confidence: 94%
“…Similar binding poses were also proposed based on molecular modelling results for the opioid fragment of other opioid/antitachykinin hybrids [ 17 ] or some Tyr- d -Ala-Phe-Phe (TAPP) derivatives [ 66 ]. Aromatic rings of BU72 (experiment [ 67 ]), fentanyl (modelling [ 68 ]) cyclic opioid derivatives (modelling [ 69 ]), or linear peptide opioids (modelling [ 70 ]) were found to be located similarly as the Phe 4 ring in MOR-1 pose. For the -NH-NH-Z- d -Trp fragment, a few quite distinct binding poses are found at MOR.…”
Section: Resultsmentioning
confidence: 99%
“…The activity of DMT-DALDA (H-Dmt-D-Arg-Phe-Lys-NH2; Dmt = 2′,6′-dimethyltyrosine), a selective mu opioid agonist, was equivalent to morphine in producing MC degranulation, although it was greater than a 1000-fold more potent in producing analgesia, suggesting a possible lower risk in producing a spinal mass at equivalent analgesic concentrations [157]. Moreover, the Dmt (2′,6′-dimethyl-L-Tyr) moiety of DMT-DALDA was found to represent the driving force for the high potency and agonist activity at the mu opioid receptor (MOR), and the key amino acid residues Y148 3.33 and Y326 7.42 were responsible for DMT-DALDA binding to MOR [158]. On the other hand, opioids can induce IgE-mediated MC degranulation.…”
Section: Opioid Peptides and Mast Cellsmentioning
confidence: 99%